Tales of the Unexpected: Doing Everyday Life, Doing Fieldwork, Doing Anthropology and Sociology - Jenkins, Richard (Anthropologica, 2013)
This article is a developed version of my keynote address to the annual meeting of the Canadian Association of Social and Cultural Anthropologists held at the University of Edmonton in May 2012. I examine the somewhat neglected, but nonetheless central, role of unexpectedness in everyday life, in order to think about how we might better deal with the unpredictable contingencies of life, theoretically and during field research. More specifically, I discuss some of the sources of uncertainty in human experience, and the role of culture as a means of suppressing uncertainty, in order to examine why ’the unexpected’ is relatively neglected in anthropology and sociol ogy. Following this I consider the analytical consequences of this neglect and—more tentatively—how we might set about remedying the situation.